PENGARUH LKPD BERBASIS PROBLEM BASED LEARNING BERMUATAN BUDAYA BATAK TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DI SMAN 1 AIR PUTIH - Zahrotun Wardah; Oktaviana Nirmala Purba (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study examines the effects of implementing Problem-Based Learning (PBL)-based worksheets integrated with Batak culture on students’ mathematical critical reasoning skills. A quantitative approach was used with a one-group pretest-posttest pre-experimental design. The research subjects were students in class XI-1 at SMAN 1 Air Putih, selected through purposive sampling. Data collection was conducted using an essay test. The analysis included a paired t-test, a normality test, and an N-gain analysis. The results showed that the data were normally distributed (pretest 0.293; posttest 0.356). The t-test yielded a significance level of 0.001 (<0.05), indicating a significant effect. The N-gain value of 0.67 falls into the moderate category, indicating an improvement in ability. Thus, PBL-based worksheets integrated with Batak culture are effective in developing students’ mathematical critical reasoning.